Design of a RoF fronthaul link based on optical generation of mm-waves for 5G C-RANs - Faris Keti; Salih M. Atroshey; Jalil A. Hamadamin (Indonesian Journal of Electrical Engineering and Computer Science, 2023)
In this paper, a cloud-radio access networks based (C-RANs) radio-over-fiber (RoF) system have been reported with the optical generation of 28 GHz and 57 GHz millimeter-wave using phase modulation and stimulated Brillouin scattering effect in optical fibers. As a result, a cost-effective system with improved performance is achieved by the proposed method. Based on the proposed scheme, a 28 GHz (licensed band) and 57 GHz (Un-licensed band) optical millimeter-waves are generated by simulation only using 14 GHz and 16 GHz radio frequency (RF) respectively. Because the performance of any optical transmission system is limited by the Q factor and the bit error rate (BER) and any input power of the laser into the fiber needs to be less than the Brillouin threshold in order to avoid the sharp degradation of the Q factor. Also, the Brillouin threshold for this study setup is determined which is around 6 dBm in the case of licensed band and 2 dBm in the case of unlicensed band. The simulation results show that the proposed scheme can provide 100 km single-mode fiber for 28 GHz and 25 km for 57 GHz with transmission rates of 10 Gbps for both of them. In addition, a stable millimeter-wave RoF link, high quality carriers, and a reduction in nonlinearity effects are achieved with the proposed scheme.